A development of E-Learning website for driving school / Hariyani Wadzir - Wadzir, Hariyani (2006)
This project is designed as an E-Leaming for Driving School that can be accessed by students and administrator through internet. The system provides services and information for students who can view personal information and can access learning courses of driving license such as exercise, tutorial and quizzes. The system provides convenient way for all students to search information, like the information about driving license. If a student has enrolled in the driving school, he or she can login the system with student id and password, and then check quizzes mark he or she has taken. The administrator can work with the system to update and delete the student's personal information. The administrator can also insert a new administration and change the password. The technologies used in the project are VBScript and Active Service Page. The database is Microsoft Access and web server is IIS, which is run on Window XP with Internet Explorer.